Intensity modulation with the “step and shoot” technique using a commercial mlc: a planning study - Keller-Reichenbecher, Mark-Aleksi; Bortfeld, Thomas; Levegrün, Sabine; Preiser, Konrad; Schlegel, Wolfgang (International journal of radiation oncology, biology, physics, 1999)
Purpose/Objective: For complex planning situations where organs at risk (OAR) surrounding the target volume place stringent constraints, intensity-modulated treatments with photons provide a promising solution to improve tumor control and/or reduce side effects. One approach for the clinical implementation of intensity-modulated treatments is the use of a multileaf collimator (MLC) in the “step and shoot” mode, in which multiple subfields are superimposed for each beam direction to generate stratified intensity distributions with a discrete number of intensity levels. In this paper, we examine the interrelation between the number of intensity levels per beam for various numbers of beams, the conformity of the resulting dose distribution, and the treatment time on a commercial accelerator (Siemens Mevatron KD2) with built-in MLC. Methods and Materials: Two typical, clinically relevant cases of patients with head and neck tumors were selected for this study. Using the inverse planning technique, optimized treatment plans are generated for 3-25 evenly distributed coplanar beams as well as noncoplanar beams. An iterative gradient method is used to optimize a physical treatment objective that is based on the specified target dose and individual dose constraints assigned to each organ at risk (brain stem, eyes, optic nerves) by the radiation oncologist. The intensity distribution of each beam is discretized within the inverse planning program into three to infinitely many intensity levels or strata. These stratified intensity distributions are converted into MLC leaf position sequences, which can be subsequently transferred via computer link to the linac console, and can be delivered without user intervention. The quality of the plan is determined by comparing the values of the objective function, dose-volume histograms (DVHs), and isodose distributions. Results: Highly conformal dose distributions can be achieved with five intensity levels in each of seven beams. The merit of using more intensity levels or more beams is relatively small. Acceptable results are achievable even with three levels only. On average, the number of subfields per beam is about 2-2.5 times the number of intensity levels. The average treatment time per subfield is about 20 s. The total treatment time for the three-level and seven-beam case with a total of 39 subfields is 13 min. Conclusion: Optimizing stratified intensity distributions in the inverse planning process allows us to achieve close to optimum results with a surprisingly small number of intensity levels. This finding may help to facilitate and accelerate the delivery of intensity-modulated treatments with the “step and shoot” technique.
Gesehen am 19.02.2019